A case report of Takayasu arteritis with aortic dissection as initial presentation. Issue 45 (November 2017) - Guo, JiGuang; Zhang, GuoWu; Tang, Dan; Zhang, JianBin
Abstract: Rationale: The initial symptoms and signs of Takayasu arteritis vary due to the heterogeneity of affected vessels. Moreover, the vascular lesions are difficult to detect at initial presentation, making diagnosis even more challenging. Although cases of aortic dissection with arteritis history have been reported, Takayasu arteritis in men with aortic dissection as initial presentation is very rare. Patient concerns: A 37-year-old man presenting with persistent chest and back pain for 6 days was transferred to our hospital for further treatment. Left hand pulse was absent and right lower limb pulse was feeble. Blood pressure was 144/83 mmHg in the right arm but only 114/62 mmHg in the left arm. Diagnoses: Computed tomography angiography revealed aortic dissection (DeBakey type III b) from the descending aorta to the distal abdominal aorta. Interventions: High-dose glucocorticoid therapy and immunosuppressive therapy have been used to control inflammatory reaction during acute period of Takayasu arteritis. Endovascular graft exclusion (EVGE) surgery was performed to cover the primary entry tear and re-expand true lumen during inactive stage. Outcomes: His pain symptoms improved progressively and he was followed in our outpatient clinic after discharged from hospital, without recurrence. Lessons: Timely therapy (glucocorticoid and immunosuppressive) and corrective surgery (endovascular graft exclusion) for Takayasu arteritis with aortic dissection at the inactive stage is essential and beneficial.